17-Year Results following Transepiphyseal Anterior Cruciate Ligament Reconstruction in Children and Adolescents - Zimmerer, Alexander; Schneider, Marco M.; Semann, Carina; Schopf, Wolfgang; Sobau, Christian; Ellermann, Andree (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Objective Rupture of the anterior cruciate ligament (ACL) in childhood and adolescence is a serious injury. It is now known that conservative therapy of an unstable knee joint in childhood or adolescence under can lead to poor subjective and objective results. The aim of this study is to record long-term results after transepiphyseal ACL reconstruction using autologous hamstring tendons and extracortical fixation in childhood and adolescence with open physes – at least 15 years after surgery.Methods Our internal registry was used to identify all patients who received surgical treatment of an acl tear during childhood and adolescence by transepiphyseal acl reconstruction more than 15 years previously. In these patients, the International Knee Documentation Committee for Subjective Knee Form (IKDCsubj.), Knee Injury and Osteoarthritis Outcome Score (KOOS), Tegner Activity Score (TAS) and Lysholm Score were collected, and clinical and magnetic resonance imaging (MRI) examinations were performed.Results A total of 22 patients were identified, 5 of whom could not be contacted. The mean age at the time of surgery was 13.1 years, and the mean follow-up time was 17.4 years. In 3 patients, a traumatic tear was observed with subsequent reconstruction of the ACL. None of the included patients showed a growth disorder during the course of the study. The IKDCsubj. was 92.4 ± 14.7 (48 – 100), the Lysholm score was 87.9 ± 16.9 (34 – 100), the TAS was 5.7 ± 2.3 (3 – 9) and the pain level based on VAS was 3.5 ± 2.6 (1 – 8) points. The values showed subjective and objective deterioration compared to the 10-year results, with no statistical significance. The following subscores were reported for the KOOS: KOOSpain 90.9 ± 17.6 (28 – 100); KOOSsymptom 82.9 ± 22.6 (11 – 100); KOOOSADL 94.3 ± 13.7 (44 – 100); KOOSSport 80.3 ± 26.4 (15 – 100); KOOSQOL 80.9 ± 25.8 (0 – 100). 13 of the 17 patients could also be clinically and radiologically examined. In 92% of patients, an intact acl reconstruction was found without evidence of cartilage or meniscus damage. The mean lateral difference in the KT-1000 measurement was 1.5 mm.Conclusion ACL reconstruction in childhood and adolescence provides good functionality and stability of the knee joint over the long term. Secondary signs of osteoarthritis can only be detected in isolated cases by MRI. ACL reconstruction using the transepiphyseal technique can be considered the method of choice for open growth plate knee joints.
Keywords: anterior cruciate ligament; long-term results; reconstruction; children; adolescents